Lack of association of vitamin D receptor gene polymorphisms with susceptibility to type 1 diabetes mellitus in the Portuguese population - Lemos, Manuel C. (2008)
The vitamin D receptor (VDR) gene is a candidate gene for susceptibility to autoimmune disorders. Association studies of VDR polymorphisms and risk of type 1 diabetes often produced conflicting results in different ethnic backgrounds. The aim of this study was to test for association between common VDR polymorphisms and the genetic susceptibility to type 1 diabetes in the Portuguese population. We genotyped 207 patients with type 1 diabetes and 249 controls for the FokI T>C (rs10735810), BsmI A>G (rs1544410), ApaI G>T (rs7975232), and TaqI C>T (rs731236) single nucleotide polymorphisms by polymerase chain reaction and restriction fragment length polymorphism analysis. The distribution of VDR genotype, allele, and haplotype frequencies did not differ significantly between patients and controls. These data suggest that the single nucleotide polymorphisms of the VDR gene are unlikely to contribute significantly to type 1 diabetes susceptibility in the Portuguese population.